Mommy tracks and public policy: on self-fulfilling prophecies and gender gaps in promotion; Selbsterfüllende Prophezeiungen und geschlechtsspezifische Karrieremöglichkeiten - Kjell Erik Lommerud; Steinar Vagstad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
Consider a model with two types of jobs. The profitability of promoting a worker to a fast-track job depends not only on his or her observable talent, but also on incontractible effort. We investigate whether self-fulfilling expectations may lead to higher promotion standards for women. If employers expect women to do more household work than men, thereby exerting less effort in their paid job, then women must be more talented to make promotion profitable. Moreover, specialization in the family will then result in women's doing most of the household work. Such self-fulfilling prophecies can be defeated: both affirmative action and family policy can make women spend more effort in the market, which can lead the economy to a non-discriminatory equilibrium. However, we find that it is unlikely that temporary policy can move the economy to a symmetric equilibrium: policy must be made permanent. Anti-discrimination policy need not enhance efficiency, and from a distribution viewpoint this is a policy with both winners and losers. – – Nach wie vor ist das Arbeitsangebot von Frauen und Männern unterschiedlich, obwohl wenig Unterschiede bei den für den Arbeitsmarkt relevanten Fähigkeiten bestehen. Wenn Arbeitgeber erwarten, dass Frauen mehr Haushaltsarbeit übernehmen und daher weniger Leistung z.B. in Form von Überstunden zeigen, müssen Frauen mehr Talent besitzen, damit sich aus Sicht des Arbeitgebers eine Beförderung auf einen höheren Karrierepfad lohnt. Dies führt dazu, dass sich Frauen auf die Familie spezialisieren und somit zu einer selbsterfüllenden Prophezeiung. Wir kommen zu dem Ergebnis, dass Anti- Diskriminierungspolitik dazu führen kann, dass das Arbeitsangebot der Frauen erweitert wird; diese Politik muss jedoch permanent sein. Unter Wohlfahrtsgesichtspunkten ist die Wirkung einer solchen Politik nicht eindeutig.
Keywords: D13; J16; J22; J71; 330; Self-fulfilling prophecies; gender discrimination; promotion